1993
DOI: 10.1002/bsl.2370110105
|View full text |Cite
|
Sign up to set email alerts
|

Sanism, social science, and the development of mental disability law jurisprudence

Abstract: This article examines the way that "sanist" attitudes (attitudes driven by the same kind of irrational, unconscious and bias-driven stereotypes exhibited in racist and sexist decisionmaking) lead to "pretextual" decisions (in which dishonest testimony is either explicitly or implicitly accepted) in mental disability law jurisprudence. In conjunction with these sanist ends, social science data is teleologically employed by legal decisionmakers, so that it is privileged when it supports a conclusion that the fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

1994
1994
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 0 publications
1
11
0
Order By: Relevance
“…This is consistent with past research including female NGRI acquittees (Breheney, Groscup, & Galietta, 2007;Hodgins, Hebert, & Baraldi, 1986). In 1993, Perlin and Dorfman (1993) contended that legal decision making can be, among other attributes, sexist when deciding mental health related cases. The current result may support that contention.…”
Section: Discussionsupporting
confidence: 85%
“…This is consistent with past research including female NGRI acquittees (Breheney, Groscup, & Galietta, 2007;Hodgins, Hebert, & Baraldi, 1986). In 1993, Perlin and Dorfman (1993) contended that legal decision making can be, among other attributes, sexist when deciding mental health related cases. The current result may support that contention.…”
Section: Discussionsupporting
confidence: 85%
“…This study implemented a mock jury paradigm to investigate one of the most stigmatized and misunderstood defenses in criminal proceedings – the insanity defense (Perlin, , , ; Perlin & Dorfman, ; Skeem & Golding, ; Vidmar & Hans, ). Previous research has suggested that insanity defense bias heavily influences decision‐making (Louden & Skeem, ; Skeem et al, ; Skeem & Golding, ), and that jurisdictional variations in legal definitions and legal standards regarding NGRI carry little predictive influence on outcomes (Finkel & Slobogin, ; Ogloff, ).…”
Section: Discussionmentioning
confidence: 99%
“…This study implemented a mock jury paradigm to investigate one of the most stigmatized and misunderstood defenses in criminal proceedingsthe insanity defense (Perlin, 1994(Perlin, , 1996(Perlin, , 2000Perlin & Dorfman, 1993;Skeem & Golding, 2001;Vidmar & Hans, 2007). Previous research has suggested that insanity defense bias heavily influences decision-making (Louden & Skeem, 2007;Skeem et al, 2004;Skeem & Golding, 2001), and that jurisdictional variations in legal definitions and legal standards regarding NGRI carry little predictive influence on outcomes (Finkel & Slobogin, 1995;Ogloff, 1991 The various experimentally constructed interactions of medication compliance, insight, and expert testimony elaboration failed to yield statistically significant predictions regarding verdict and meta-responsibility, with one exception.…”
Section: Discussionmentioning
confidence: 99%
“…By teleological, we refer to outcome-determinative reasoning; social science that enables judges to satisfy predetermined positions are privileged, whilst data that would require judges to question such ends are rejected or subordinated (see Perlin, 1993Perlin, , 1993Perlin, -1994aPerlin & Dorfman, 1993). In other words, 'social science data is used and misused for teleological ends .…”
Section: Teleology Pretextuality and Sanismmentioning
confidence: 98%